Clinical value of intra-operative ultrasonography during laparoscopic cholecystectomy - Pesce, Antonio; Portale, Teresa Rosanna; Stefano, Biagio Di; Costa, Salvatore; Cammisuli, Fernando (Laparoscopic Surgery, 2018)
The correct identification of biliary anatomy and bile duct injury (BDI) prevention represent important topics of debate in laparoscopic cholecystectomy (LC), which is considered the first widely accepted “gold standard” laparoscopic approach in general surgery. The article entitled “Laparoscopic ultrasonography as an alternative to intra-operative cholangiography during laparoscopic cholecystectomy” is an interesting review analyzing the clinical value of intra-operative laparoscopic ultrasound (LUS) during cholecystectomy.